In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Hydrogen generation with CO2 utilization: a solvay cluster study - Kale, Ganesh R.; Kulkarni, Bhaskar D. (International Journal of Hydrogen Energy, 2013)
The fuel cell economy is yet to start research programs in hydrogen generation with CO2 utilization for hydrocarbon reforming processes used in fuel processor applications. A simple thermodynamic study using solvay clusters was done to investigate the feasibility of using the carbon species produced in the steam methane reforming process to produce value added chemicals. The results of this study are highly encouraging to start process development of closed systems of hydrogen generation with CO2 conversion to acetic acid/acrylic acid making easier the commercialization of fuel cells and hydrogen energy. Such studies can be specifically carried out for different fuel processor systems. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CO2 utilization; Fuel processing; Gibbs energy; Solvay clusters; Steam reforming

Activation by pretreatment of Ag-Au/Al2O3 bimetallic catalyst to improve low temperature HC-SCR of NOx for lean burn engine exhaust - More, Pavan M.; Nguyen, Duy L.; Granger, Pascal; Dujardin, Christophe; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2015)
Bimetallic Ag-Au/Al2O3 catalyst was synthesised by successive impregnation of 1% Au and 1% Ag on in-house prepared high surface area alumina (450 m(2)/g). The corresponding monometallic catalysts were also prepared by loading 1% Ag or 1% Au on the same high surface area alumina for comparison. The catalysts were characterised by various physico-chemical techniques and tested for SCR activity under lean burn engine exhaust conditions. Ag-Au/Al2O3 catalyst prepared by successive impregnation method showed considerably higher NO reduction (100%) to N-2 compared to 1% Au/Al2O3 (70%) whereas the activity was comparable with that of 1% Ag/Al2O3 (96%). The effect of various pretreatments on SCR activity of Ag-Au/Al2O3 was studied and pretreatment at 250 degrees C in flow of hydrogen was found to give the best results with 100% NO conversion to N-2 at 353 degrees C. Further ageing of the catalyst under reaction feed at 500 degrees C resulted in considerable increase in low temperature activity of bimetallic catalyst with similar to 40% NO conversion at 222 degrees C. Even though the SCR activity of pretreated Ag-Au/Al2O3 and Ag/Al2O3 were comparable, after ageing the Ag-Au/Al2O3 showed significantly higher NO conversion (95%) compared to Ag/Al2O3 (83%) and Au/Al2O3 (70%). The formation of H-2 and CO due to steam reforming of higher hydrocarbon (decane) was evidenced at the temperature of highest deNO(x) activity. Detailed investigation of the textural properties of the pretreated and aged catalysts showed presence of well dispersed metallic Au and Ag-n(delta+) clusters after pretreatment in hydrogen at 250 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag-Au bimetallic catalyst; Catalyst ageing; dispersion; Low temperature HC-SCR; Steam reforming

Highly loaded well dispersed stable Ni species in NiXMg2AlOY nanocomposites: application to hydrogen production from bioethanol - Fang, Wenhao; Paul, Sebastien; Capron, Mickael; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (Applied Catalysis B-Environmental, 2015)
Inexpensive NiXMg2AlOY nanocomposites with high Ni content (Ni wt% > 40%) are developed as efficient catalysts for the sustainable hydrogen production from a mixture of ethanol and water at low temperature. The NiXMg2AlOY nanocomposites are composed of small and uniform nanoparticles (4-6 nm) of NiO, Ni-Mg-(Al)-O and/or MgO. The strong interactions existing between Ni2+ cations and Mg2+ and/or Al3+ cations either in the Ni-Mg-(Al)-O solid solution and/or at the interface of nanoparticles of NiO and/or Ni-Mg-(Al)-O make the catalyst highly active and stable. The behavior of the solids is analyzed in the presence of low and high concentrations of ethanol while maintaining a H2O/EtOH molar ratio of 3. The NiXMg2AlOY catalysts are shown to be efficient toward H-2 production between 250 and 650 degrees C. In the presence of low concentration of ethanol, on the highly loaded Ni compound (Ni12Mg2AlOY), total conversion of ethanol is obtained at 250 degrees C without formation of CO and carbon, and at 300 degrees C a H-2 yield of 3 mol moletEtOH(-1) is obtained without the formation of CO, exhibiting a remarkable stability with the time on stream even if some carbon is formed. In high concentration of ethanol, total conversion of ethanol is obtained at 450 degrees C on the highly loaded Ni compound (Ni12Mg2AlOY). In such conditions, a stable co-generation of carbon nanofibrous materials which amount increases with Ni content is also obtained. The catalytic stability is related to the type and morphology of the carbon species formed. The correlations among the catalyst properties, the catalytic performances and the characterizations are thoroughly discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrogen; Nanofibrous carbon; nickel oxide; Steam reforming

Tuning the dimensionality of layered Srn+1Tin−xNixO3n+1 perovskite structures for improved activity in syngas generation - Dama, Srikanth (Journal of Catalysis, 2018)
Interest in perovskite type oxides is growing due to their versatile catalytic applications. A series of Ruddlesden-Popper (RP) type layered perovskite oxides Srn+1Tin−xNixO3n+1 were prepared and evaluated for their catalytic activity in steam reforming, CO2 reforming and bi-reforming of methane. These materials, prepared through citrate gel method were characterized to understand their structure and Ni reducibility. Substitution of Ni in RP phases was established through refinement of XRD powder pattern. During methane reforming, the catalytic activity increased with the order of RP phase of SrTi1−xNixO3−δ (n = ∞). TPR results show variation in Ni reducibility with the order of RP phase, while TPD-O2 study helped to estimate oxygen vacancies. These vacancies seem to influence catalytic activity during methane reforming. Transient pulse experiments show that CO2 dissociates over oxygen vacancies to give CO and oxygen, with later replenishing lattice oxygen in SrTi0.8Ni0.2O3−δ (n = ∞) phases. Highly labile oxygen vacancies generated in the bulk of SrTi0.8Ni0.2O3−δ must be migrating to the surface, helping in the removal of coke formed. Characterization of catalysts after reaction helped in better understanding of coke precursors.
Keywords: Dry reforming; NickelSyngas; Ruddlesden-Popper (RP) perovskites; Steam reforming